2020
DOI: 10.7554/elife.56907
|View full text |Cite
|
Sign up to set email alerts
|

High glucose levels increase influenza-associated damage to the pulmonary epithelial-endothelial barrier

Abstract: Diabetes mellitus is a known susceptibility factor for severe influenza virus infections. However, the mechanisms that underlie this susceptibility remain incompletely understood. Here, the effects of high glucose levels on influenza severity were investigated using an in vitro model of the pulmonary epithelial-endothelial barrier as well as an in vivo murine model of type II diabetes. In vitro we show that high glucose conditions prior to IAV infection increased virus-induced barrier damage. This was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
(90 reference statements)
2
18
0
1
Order By: Relevance
“…In the non-alveolar epithelium, damaged ciliated cells lead to reduced mucociliary clearance capacity ( 282 , 283 ), and compromised integrity of tight junctions increases paracellular flux of glucose into the ASL ( 117 , 207 ), escalating the damage through the numerous mechanisms described before (see Figure 20 ). This is in agreement with a recent publication on IAV infection showing that elevated glucose prior to viral infection increases virus-induced pulmonary barrier damage ( 284 ). Host cell damage together with elevated glucose turns negative feedback homeostatic mechanisms into a positive feedback loop of pathological processes.…”
Section: Resultssupporting
confidence: 93%
“…In the non-alveolar epithelium, damaged ciliated cells lead to reduced mucociliary clearance capacity ( 282 , 283 ), and compromised integrity of tight junctions increases paracellular flux of glucose into the ASL ( 117 , 207 ), escalating the damage through the numerous mechanisms described before (see Figure 20 ). This is in agreement with a recent publication on IAV infection showing that elevated glucose prior to viral infection increases virus-induced pulmonary barrier damage ( 284 ). Host cell damage together with elevated glucose turns negative feedback homeostatic mechanisms into a positive feedback loop of pathological processes.…”
Section: Resultssupporting
confidence: 93%
“…The influenza A virus (IAV) induces a self-limited infection in most patients, which is characterized by several symptoms such as myalgia, fever, and dry cough ( 130 ). Nevertheless, patients with diabetes experience a more severe type of this disease ( 131 ) that is represented by a triple risk of hospitalization and double risk of fatality compared with non-diabetic sufferers ( 132 ). Despite the fact that IAV infects upon 15% of the world's population every year ( 133 ), the full mechanisms underlying its pathogenesis, especially on patients with diabetes, remain thus far inconclusive.…”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
“…Despite the fact that IAV infects upon 15% of the world's population every year ( 133 ), the full mechanisms underlying its pathogenesis, especially on patients with diabetes, remain thus far inconclusive. In this sense, Hulme et al ( 132 ) reported that the IAV infection in hyperglycemic conditions increases the endothelial damage leading to a pronounced inflammatory response; this explains, at least in part, the severity of the symptoms in patients with diabetes ( 132 ). In support of this notion, Kohio and Adamson ( 134 ) reported an enhanced IAV replication rate in pulmonary epithelial cells under elevated glucose concentrations in vitro .…”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Viral and host RNA was extracted from mouse lung samples, cDNA was synthesised, and real-time PCR was performed as described previously ( Hulme et al, 2020 ). Forward and reverse primers used in the present study are supplied in Supplementary file 1 .…”
Section: Methodsmentioning
confidence: 99%